Gold in Investment Portfolio from Perspective of European Investor - Šoja, Tijana (The European Journal of Applied Economics, 2019)
Gold is a unique asset, highly liquid, but scarce and limited. It is a luxury good and can be considered an investment opportunity. Gold is an asset which does not carry counterparty risk – there is no associated credit risk. Due to these characteristics, gold represents a significant asset, and has a fundamental role in investment portfolios. These circumstances increase the interests of investors to include gold in investment port-folios, especially during times of financial crisis. If an investor decides to include gold in investment portfolio, it is necessary to evaluate the portion of gold in the portfolio considering risk aspect, return and diversification. In this research, a  hypothesis was tested and confirmed that gold offers good diversification for the investment portfolio, which implies that gold is a desirable asset in the investment portfolio. This research is focused on developing an optimal portfolio that com-bines the Eurozone bond index with the investment grade rating from 1 to 10 years (EG05), the stock index Euro Stoxx50 and gold using the Markowitz methodology. The result showed that optimal portfolio should include gold with a share between 1% to 9%, depending on the risk that the investor is willing to accept.